P‐88: Properties of Liquid‐Crystal Mixtures Containing Methoxy‐Bridge Polar Monomers and Olefinic‐Chain Polar Monomers. Issue 1 (28th June 2021) - Miao, Jie; Ren, Gui-Ning; Zhao, Guo; Song, Yan-Jun; Hsieh, Chung-Ching; Xiao, Jun-Cheng; Zhao, Bin
Abstract : Methoxy‐bridge polar monomer has high dielectric anisotropy, which can reduce the driving voltage of the panel and save energy; olefinic‐chain monomer can effectively reduce the rotational viscosity and improve the response speed of the panel, while the polar alkene monomer has both low rotational viscosity and high dielectric anisotropy, which has a good application prospect. At present, the industry does not have too much verification and analysis of the collocation about the collocation of two monomers. In this paper, the reliability of liquid crystal materials containing polar methoxide monomers and polar alkene monomer was tested. The results showed that VHR (Voltage Holding Ratio) performance was worse in the experimental group with the two monomers. And with the extension of UV irradiation time, the difference between the experimental group and the control group was more obvious. A further test of IS (Image Sticking) was conducted on a 32‐inch display platform. The results showed that the liquid crystal containing both two monomers was tested NG, while the control group was OK.